Opera Batak Sisingamangaraja XII Episode Ugamo Malim Horja Bolon Na Parpudi: Usungan Tradisi dan Kontemporer - Enrico Alamo; Rosta Minawati; Sulaiman Sulaiman; Sherli Novalinda (Institut Seni Indonesia Yogyakarta, 2020)
Batak Opera of Sisingamangaraja XII the Episode of Ugamo Malim Horja Bolon Na Parpudi: Carriying out the Tradition and Contemporary. The purpose of research and creation of Batak opera is to revitalize Batak traditional arts. Sisingamangaraja Opera Batak XII, the episode of Ugamo Malim Horja Bolon Na Parpudi, results from the research and creation of the Sisingamangaraja XII Batak opera. The creation of Batak opera uses research methods, namely observation, interviews, literature study, and documentation. The working process begins with reading the script, making blocks according to the script, detailing blocking, playing the role/scenes, music, and tutoring, selecting and doing the artistic and lighting creation. Opera Batak was done in contemporary work, including story elements, jokes (amalopas), and even accompaniment (uning-uning). Sisingamangaraja Opera Batak XII, the episode of Ugamo Malim Horja Bolon Na Parpudi tells the story of Ugamo Malim in the Dutch colonial era and the family of King Sisingamangaraja XII. The story’s plot consists of; news of the death of King Sisingamangaraja XII, the captivity of the Sisingamangaraja XII family, Ompu Ni Onggung, and Ompu Portahan Batu, who had a grudge against King Sisingamangaraja XII and followers of Ugamo Malim’s teachings. Tortor dance and Cawan dance were created contemporary. Sisingamangaraja Batak Opera XII, the episode of Ugamo Malim Horja Bolon Na Parpudi wants to maintain the existence and preserve the traditional arts of the Batak community.Keywords: Batak opera; Sisingamaraja XII; ugamo malim; tortor